Morphological study and exopolysaccharide production of Malaysian Ganoderma lucidum mycelium in a batch fermentation / Sugenendran Supramani - Sugenendran , Supramani (2019)
A slow-growing cultivated Ganoderma lucidum QRS 5120 (GLQ5) was identified from a commercial mushroom farm. The fungus was identified morphologically by standard Basidiomycete characteristics (colour, fruiting body type, hymenium pores, basidiospores, plate growth) and molecular tools. In molecular identification, the fungus was compared with top-10 similarity of National Centre for Biotechnology Information – Basic Local Alignment Search Tool (NCBI-BLAST) once the tissue culture procedure succeeded. The phylogenetic tree was then constructed using Molecular Evolutionary Genetic Analysis 10 (MEGA-X) and verified using plasmid Editor (ApE) software (100% matched with G. lucidum strain 39). Upon isolation and identification, preliminary studies were conducted on GLQ5 mycelium. Exopolysaccharide (EPS) and intracellular polysaccharide (IPS) in a controlled shake-flask fermentation were studied at different initial pHs (3, 4, 5, and 6). At initial pH 4, the productivity of both EPS (0.071 g/L day-1) and IPS (0.046 g/L day-1) were the highest possessing ovoid-pellets morphology. Such pH condition also generated 5.13 g/L of biomass, 2.64 g/L EPS and 1.46 g/L IPS higher than initial pH 5 and pH 6 conditions. Initial pH 4 also produced higher carbohydrate contents in both EPS (0.435 g/L) and IPS (0.191 g/L). Then, using the preliminary studies as the reference, response surface methodology (RSM) was done to study the interaction between initial pH, initial glucose concentration and agitation rate for production of biomass-EPS-IPS from GLQ5 in submerged fermentation (SmF). A central composite design (CCD) was applied, and the polynomial model was fitted to the experimental data. The model was significant in all parameters investigated. Initial pH showed the strongest effect (p < 0.0001) for biomass, EPS and IPS production, meanwhile agitation showed iv significant value (p < 0.005) for biomass. The model was validated by applying the optimized conditions and generated 5.12 g/L of biomass (initial pH 4.01,32.09 g/L of glucose and 102.45 rpm), 2.49g/L EPS (initial pH 4, 24.25 g/L of glucose and 110 rpm) and 1.52 g/L of IPS (and initial pH 4, 40.43 g/L of glucose, 103 rpm) in 500-mL shake flask fermentation. By using the optimised media, the productive pellet morphology was determined. At day 9 (hairy-ovoid pellet), the biomass was the highest. At day 11 (hairy-sphere pellets), EPS was highest, and at day 13 (sphere pellets), IPS was the highest. Meanwhile, in a 2-L stirred-tank bioreactor (STR), 1.9-fold higher of biomass (9.75 g/L: smooth pellets) was generated and 2.1-fold higher EPS (5.43 g/L: ovoid-hairy pellets) compared to shake flask. Then, the molecular characterisation of EPS was studied using Proton Nuclear Magnetic Resonance (1H NMR) and Fourier Transform Infrared Spectroscopy (FTIR). The EPS showed the characteristics of β-glycosidic linkages in FTIR at 925 cm-1, 1635 cm-1, 1077 cm-1,920 cm-1, 800 cm-1, and in 1H NMR at  4.58, 3.87, 3.8. The result indicated that EPS was composition of 1-3-β-D-linkages. Finally, the bioactivity of the EPS was screened against common pathogenic bacteria. The zone of inhibition showed EPS possessed antimicrobial against Escherichia coli (33.32 mm), Serratia marcescens (24.58 mm), Staphylococcus aureus (39.23 mm), and Staphylococcus epidermidis (35.3 mm). EPS was also positive against Aspergillus niger for antifungal-demelanizing activity. The result showed that the antifungal-demelanizing activity of EPS is dose-dependent. Together, the research managed to design an ‘’upstreaming and downstream processing’’ blueprint for bioactive production of EPS to be applied in large-scale fungal-based bioprocessing.